Apachean Origins: New Explorations of the Canadian Heritage of A.D. 13th Century Dene at Promontory Point, Utah ... - Ives, John (University of Alberta Library, 2011)
SSHRC Awarded IG 2012: The proposed archaeological research focuses on Apachean migration as a significant vector of Dene expansion in western North America. Renewed archaeological thinking about migration pays attention to social science research into migration, and specific processes like kin structuring of founding populations. The current proposal develops predictions about what to expect during Apachean migration and uses the extraordinary fidelity of Promontory material culture and the growing inventory of AMS dates reflecting temporal trends to frame precise questions. These include insights into the population structure of the Promontory Cave inhabitants (derived from moccasin sizes and their precise relationship to stature and age), assessing the potential for apex founding populations (based on refinement of moccasin sewing techniques) and similar problems. ...